Multi-element high-activity element coating capable of forming self-repairing Al2O3 protective layer in non-oxygen-control lead bismuth alloy and preparation method of multi-element high-activity element coating
By using powder burying heating method and liquid lead-bismuth alloy soaking technology to form a self-healing Al2O3 protective layer, the problem of liquid metal corrosion in non-oxygen controlled environments is solved and efficient corrosion protection for the substrate is achieved.
Patent Information
- Application Number
- CN202411621529.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-14
AI Technical Summary
The prior art is difficult to effectively prevent liquid metal corrosion in lead-bismuth alloys, especially in non-oxygen controlled environments, resulting in shortening of material life and instability of the system.
The FeCrAl coating containing Fe-Cr, Fe-Al, Cr-Al, Fe-Cr-Al phases was formed on the substrate surface by powder burying heating, and a self-healing Al2O3 protective layer was formed by immersion of liquid lead-bismuth alloy to prevent Invasion of dissolved oxygen and Pb-Bi and dissolution leaching of alloy elements.
The formation of a dense, stable and strong adhesion Al2O3 oxide layer in non-oxygen lead-controlled bismuth alloy is achieved, effectively preventing oxidative corrosion, extending material life, and reducing the cost and complexity of corrosion protection.
Smart Images

Figure CN119491222A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of liquid metal corrosion protection, and specifically relates to a multi-element high-activity coating for forming a self-repairing Al2O3 protective layer in a non-oxygen-controlled lead-bismuth alloy and a preparation method thereof. Background Art
[0002] Lead-bismuth eutectic (LBE) has become a leading candidate material for coolant in accelerator driven systems (ADS) and lead-cooled fast reactors (LFR) due to its favorable thermophysical and chemical properties, including excellent neutronics, radiation resistance, heat transfer performance, and chemical inertness. However, materials exposed to LBE are subject to liquid metal corrosion attacks (such as oxidation, dissolution, pitting, erosion, etc.) depending on the exposure conditions (oxygen concentration, temperature, exposure time, flow rate, etc.). Therefore, it is crucial to propose solutions to overcome all these challenges in order to increase the lifetime of materials exposed to LBE and make the system more viable and efficient. LBE corrosion of container and structural materials is a key challenge in the use of LBE in ADS and advanced nuclear reactors, and a full understanding of its important properties and corrosion protection is essential for the proper design and safe operation of LBE heat transfer loops.
[0003] The design idea of corrosion-resistant coating in LBE environment is mainly to form a dense self-passivating oxide film in LBE with a certain oxygen content to protect the substrate by adding oxide-forming elements (such as Fe, Al, Cr, Si), preventing the matrix elements from dissolving outward and blocking the inward diffusion and penetration of lead and bismuth. From the perspective of comprehensive performance and future engineering applications, ceramic coatings and multi-element coatings (FeAl-based) have good application potential. Hard ceramic coatings are suitable for main pump impeller blades with high requirements for flow rate and wear resistance, and FeAl-based coatings are more suitable for fuel cladding tubes and steam generator heat transfer tubes. Therefore, corrosion-resistant coatings can meet the urgency of engineering needs and are a solution to the corrosion of high-temperature and high-burnup LFR materials in the future. Surface coatings containing highly active elements (such as Al and Cr) help to form a thin, continuous, dense, stable and highly adhesive oxide layer as a diffusion barrier to prevent dissolution attacks inside the LBE. However, most of the above coatings are prepared on the surface of the substrate material by spraying, magnetron sputtering, multi-arc ion plating, electroplating and other methods, and their corrosion protection performance is difficult to improve. For example, although cladding and laser remelting technologies can achieve metallurgical bonding of the coating substrate, the technical disadvantage is that they will dilute the alloy components of the substrate surface and the cladding layer; coatings prepared by plasma spraying, CVD, PVD and electrochemical deposition are easy to peel off, and the bonding strength of the prepared coatings is relatively weak; the equipment used in technologies such as GESA is complex and costly; there is a large difference in the thermal expansion coefficient between the ceramic coating and the substrate material, and thermal stress may cause cracking and peeling of the coating (Journal of Materials Review, 2022, 36(23): 21090168). Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a multi-element high-activity coating that forms a self-repairing Al2O3 protective layer in a non-oxygen-controlled lead-bismuth alloy in view of the deficiencies of the above-mentioned prior art. The method uses a powder burying heating method to introduce highly active elements Al and Cr, and combines a liquid lead-bismuth alloy immersion method to form an Al2O3 oxide layer as a diffusion barrier, preventing dissolved oxygen and Pb-Bi from invading the grain boundaries and dissolving and leaching alloy elements into the LBE, playing a role in isolating the liquid metal from the metal matrix, preventing further oxidative corrosion, and achieving corrosion protection for the matrix, solving the corrosion problem of problematic structural materials in lead-bismuth alloys.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a multi-element high-activity coating for forming a self-repairing Al2O3 protective layer in a non-oxygen-controlled lead-bismuth alloy, characterized in that a FeCrAl coating containing Fe-Cr, Fe-Al, Cr-Al, and Fe-Cr-Al phases is prepared on a substrate containing Fe, and then immersed in a liquid lead-bismuth alloy to generate a protective Al2O3 oxide layer on the surface of the coating. The method comprises the following steps:
[0006] Step 1: Pre-grind and polish the substrate surface, then perform ultrasonic cleaning and drying;
[0007] Step 2: burying the dried matrix in step 1 into uniformly mixed powders containing Al and Cr, and then placing it in a stainless steel container and sealing it;
[0008] Step 3, placing the sealed stainless steel container in step 2 in a heating furnace and filling it with protective gas, then heating it to 850°C to 900°C and keeping it for 2h to 3h, cooling it to room temperature with the furnace, and taking it out to obtain a substrate with a multi-element high-activity element coating;
[0009] Step 4: immersing the substrate with the multi-element high-activity element coating obtained in step 3 in a liquid lead-bismuth alloy at 500° C. to 600° C. for 24 h to 100 h to form a protective Al2O3 oxide layer on the surface of the coating;
[0010] Step 5: Take out the substrate with the multi-element high-activity coating after soaking in step 4, soak it in a lead-bismuth alloy cleaning solution for 2h to 3h, then take it out and dry it to obtain a multi-element high-activity coating that forms a self-repairing Al2O3 protective layer.
[0011] In actual operation, if there are multiple substrates embedded in the Al and Cr powders in step 2, it is necessary to maintain a sufficient distance between the substrates to ensure the preparation effect of the coating.
[0012] The above-mentioned method for preparing a multi-element high-activity coating that forms a self-repairing Al2O3 protective layer in a non-oxygen-controlled lead-bismuth alloy is characterized in that the substrate described in step one is ferrite / martensitic steel. Fast reactor materials include commercial austenitic stainless steel (such as 316L, 304L and 15-15Ti) and ferrite / martensitic steel (such as T91, HT-9, P22), etc. Considering the application basis and reactor construction cost in the nuclear energy field, commercial austenitic stainless steel and ferrite / martensitic steel are still the first structural materials for accelerator driven systems (ADS) and lead-cooled fast neutron reactors (LFR). The preferred substrate of the present invention ensures that the coating preparation method is applicable to fields such as corrosion protection of nuclear reactor structural materials.
[0013] The above-mentioned method for preparing a multi-element high-activity coating for forming a self-repairing Al2O3 protective layer in a non-oxygen-controlled lead-bismuth alloy is characterized in that the Al and Cr powders in step 2 include the following components in mass percentage: Al 15% to 17%, Cr 15% to 17%, and the balance is Al2O3. The present invention uses an inert substance Al2O3 as a filler to disperse the Al and Cr powders to prevent the Al and Cr powders from adhering to the surface of the substrate at the high temperature of the infiltration metal during the subsequent powder burying heating process, thereby reducing the uniformity and surface finish of the infiltration layer.
[0014] The above-mentioned method for preparing a multi-element high-activity coating for forming a self-repairing Al2O3 protective layer in a non-oxygen-controlled lead-bismuth alloy is characterized in that the pressure is maintained at 0.15MPa during the heating and cooling process in step 3. By controlling the heating and cooling process to be in a slightly positive pressure state, oxygen and other gases in the air are prevented from entering the sealed stainless steel container to affect the growth of the powder buried infiltration layer.
[0015] The above-mentioned method for preparing a multi-element high-activity coating that forms a self-repairing Al2O3 protective layer in a non-oxygen-controlled lead-bismuth alloy is characterized in that the protective gas in step three is high-purity argon with a mass purity higher than 99.99%.
[0016] The above-mentioned method for preparing a multi-element high-activity coating for forming a self-repairing Al2O3 protective layer in a non-oxygen-controlled lead-bismuth alloy is characterized in that the heating rate in step 3 is 10°C / min. By controlling the heating rate of the powder embedding heating process, the thickness and phase composition of the multi-element high-activity coating on the substrate surface are controlled to ensure the generation of a continuous, dense FeCrAl coating with appropriate thickness, and to avoid the influence of too high or too low heating rate on the growth of the coating.
[0017] The above-mentioned method for preparing a multi-element high-activity coating that forms a self-repairing Al2O3 protective layer in a non-oxygen-controlled lead-bismuth alloy is characterized in that the liquid lead-bismuth alloy in step 4 is a saturated oxygen concentration. By controlling the oxygen in the liquid lead-bismuth alloy to be a saturated oxygen concentration, a complete protective Al2O3 oxide layer is promoted to be formed on the coating surface as soon as possible. It is very convenient to achieve "saturated oxygen concentration". LBE is a saturated oxygen concentration in the air, and there is no need to add additional oxygen or control the oxygen content.
[0018] The above-mentioned method for preparing a multi-element high-activity coating that forms a self-repairing Al2O3 protective layer in a non-oxygen-controlled lead-bismuth alloy is characterized in that the lead-bismuth alloy cleaning solution in step four is prepared by CH3COOH, H2O2 and C2H5OH in a volume ratio of 1:1:1.
[0019] At the same time, the present invention also discloses a multi-element high-activity coating that forms a self-repairing Al2O3 protective layer in a non-oxygen-controlled lead-bismuth alloy, characterized in that it is prepared by the above method.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] 1. The present invention first forms a FeCrAl coating containing Fe-Cr, Fe-Al, Cr-Al, and Fe-Cr-Al phases on the surface of a substrate by a powder burying heating method, and then immerses the coating in a liquid lead-bismuth alloy, so that the strong oxide-forming element Al in the coating forms a dense structure film of an Al2O3 protective layer with a self-healing effect in the lead-bismuth eutectic (LBE), giving full play to the characteristics of Al2O3 being insoluble in LBE, having low ion mobility, and having excellent mechanical properties, preventing dissolved oxygen and Pb-Bi from invading the grain boundaries and dissolving and leaching alloy elements into the LBE, playing a role in isolating the liquid metal from the metal substrate, preventing further oxidative corrosion, and achieving corrosion protection for the substrate.
[0022] 2. The present invention introduces highly active elements Al and Cr into the coating, and utilizes Cr to improve the activity of Al, which helps to form a thin, continuous, dense, and stably attached Al2O3 oxide layer in the liquid lead-bismuth alloy as a diffusion barrier to prevent the dissolution attack of Pb-Bi; at the same time, since the Al2O3 oxide layer has good heat resistance, high density, and very low Gibbs energy, it can serve as a barrier for the diffusion of dissolved oxygen, effectively organize deeper oxidation, further improve the corrosion resistance of the coating in LBE, protect the ferrite / martensitic steel matrix from dissolution erosion, internal oxidation, and diffusion of Fe through the surface, and enhance the corrosion protection of the matrix.
[0023] 3. Different from the existing protection method of directly controlling the oxygen concentration dissolved in LBE to form a dense oxide layer on the substrate surface to slow down the diffusion and dissolution of material component elements into LBE, the present invention prepares a coating on the surface of the structural material to avoid direct contact between LBE and the structural material. There is no need to control the oxygen concentration in LBE. It only needs to be maintained at a saturated oxygen concentration under normal conditions, thus realizing a non-oxygen controlled preparation process with low cost and simple control process, which is easy to realize large-scale application.
[0024] 4. The preparation method of the present invention is simple, easy to operate, has low requirements on equipment, and the prepared coating is metallurgically bonded to the substrate, is not easy to fall off, has a large coating thickness, and has good surface quality. A uniform coating can be obtained on the surface of a workpiece with complex shapes. It is suitable for various parts with complex shapes, has a wide range of applications, and has high practical value.
[0025] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a cross-sectional morphology diagram of a substrate having a multi-element high-activity coating prepared in Example 1 of the present invention.
[0027] Figure 2 This is the surface XRD spectrum of the multi-element high-activity coating prepared in Example 1 of the present invention.
[0028] Figure 3 This is the surface XRD spectrum of the multi-element high-activity coating forming the self-repairing Al2O3 protective layer prepared in Example 1 of the present invention.
[0029] Figure 4 This is the surface XRD spectrum of the multi-element high-activity coating forming the self-repairing Al2O3 protective layer prepared in Example 2 of the present invention.
[0030] Figure 5 This is the surface XRD spectrum of the multi-element high-activity coating forming the self-repairing Al2O3 protective layer prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0031] Example 1
[0032] This embodiment includes the following steps:
[0033] Step 1: Pre-grind and polish the surface of the ferrite / martensitic steel T91 substrate, then ultrasonically clean and dry it;
[0034] Step 2: bury the ferrite / martensitic steel T91 matrix dried in step 1 in the uniformly mixed Al and Cr powders, and keep a sufficient distance between the matrixes, and then place it in a stainless steel container and seal it; the Al and Cr powders include the following components in mass percentage: Al 16%, Cr 16%, and the balance is Al2O3;
[0035] Step 3, placing the sealed stainless steel container in step 2 in a heating furnace and filling it with high-purity argon gas, maintaining the pressure at 0.15 MPa, then heating to 870°C at a rate of 10°C / min and keeping the temperature for 2.5 hours, cooling to room temperature with the furnace, and taking out a substrate with a multi-element high-activity element coating, wherein the coating contains Fe-Cr, Fe-Al, Cr-Al, and Fe-Cr-Al phases;
[0036] Step 4: immerse the substrate with the multi-element high-activity element coating obtained in step 3 in a 550° C. saturated oxygen concentration liquid lead-bismuth alloy for 24 hours to form a protective Al2O3 oxide layer on the surface of the coating;
[0037] Step 5. Take out the substrate with the multi-element high-activity coating after immersion in step 4, place it in a lead-bismuth alloy cleaning solution prepared by CH3COOH, H2O2 and C2H5OH in a volume ratio of 1:1:1, soak it for 3 hours, then take it out and dry it to obtain a multi-element high-activity coating that forms a self-repairing Al2O3 protective layer.
[0038] Figure 1 The cross-sectional morphology of the substrate with multi-element high-activity coating prepared in this embodiment is shown in FIG. Figure 1 It can be seen that the coating is tightly bonded to the substrate and the interior of the coating is dense and uniform.
[0039] Figure 2 The surface XRD pattern of the multi-element high-activity coating prepared in this example is as follows: Figure 2 It can be seen that the coating contains Fe-Cr, Fe-Al, Cr-Al, and Fe-Cr-Al phases, and no diffraction peaks of other substances or matrix appear.
[0040] Example 2
[0041] The difference between this embodiment and embodiment 1 is that the soaking time in step 4 is 48 hours.
[0042] Example 3
[0043] The difference between this embodiment and embodiment 1 is that the soaking time in step 4 is 72 hours.
[0044] Figure 3 to Figure 5The surface XRD patterns of the multi-element high-activity coatings forming the self-repairing Al2O3 protective layers prepared in Examples 1 to 3 are shown in FIG. Figure 3 to Figure 5 It can be seen that after being immersed in liquid lead-bismuth alloy with saturated oxygen concentration, in addition to the original Fe-Cr, Fe-Al, Cr-Al, and Fe-Cr-Al phases, a large number of Al2O3 diffraction peaks were detected on the surface of the coating, indicating that after the coating was exposed in the liquid lead-bismuth alloy, Al and Cr were enriched at the grain boundaries through short-range diffusion, and then oxidized to form layered Al2O3, which hindered the inward diffusion of O. These oxides became the key to improving the corrosion resistance of the substrate.
[0045] Example 4
[0046] This embodiment includes the following steps:
[0047] Step 1: Pre-grind and polish the surface of the ferrite / martensitic steel T91 substrate, then ultrasonically clean and dry it;
[0048] Step 2: bury the ferrite / martensitic steel T91 matrix dried in step 1 in the uniformly mixed Al and Cr powders, and keep a sufficient distance between the matrixes, and then place it in a stainless steel container and seal it; the Al and Cr powders include the following components in mass percentage: Al 15%, Cr 17%, and the balance is Al2O3;
[0049] Step 3, placing the sealed stainless steel container in step 2 in a heating furnace and filling it with high-purity argon, maintaining the pressure at 0.15 MPa, then heating to 900°C at a rate of 10°C / min, keeping the temperature for 3 hours, cooling to room temperature with the furnace, and taking out a substrate with a multi-element high-activity element coating, wherein the coating contains Fe-Cr, Fe-Al, Cr-Al, and Fe-Cr-Al phases;
[0050] Step 4: immersing the substrate with the multi-element high-activity element coating obtained in step 3 in a 500° C. saturated oxygen concentration liquid lead-bismuth alloy for 100 hours to form a protective Al2O3 oxide layer on the surface of the coating;
[0051] Step 5. Take out the substrate with the multi-element high-activity coating after immersion in step 4, place it in a lead-bismuth alloy cleaning solution prepared by CH3COOH, H2O2 and C2H5OH in a volume ratio of 1:1:1, soak it for 3 hours, then take it out and dry it to obtain a multi-element high-activity coating that forms a self-repairing Al2O3 protective layer.
[0052] Example 5
[0053] This embodiment includes the following steps:
[0054] Step 1: Pre-grind and polish the surface of the ferrite / martensitic steel T91 substrate, then ultrasonically clean and dry it;
[0055] Step 2: bury the ferrite / martensitic steel T91 matrix dried in step 1 in the uniformly mixed Al and Cr powders, and keep a sufficient distance between the matrixes, and then place it in a stainless steel container and seal it; the Al and Cr powders include the following components in mass percentage: Al 17%, Cr 15%, and the balance is Al2O3;
[0056] Step 3, placing the sealed stainless steel container in step 2 in a heating furnace and filling it with high-purity argon gas, maintaining the pressure at 0.15 MPa, then heating to 850°C at a rate of 10°C / min and keeping the temperature for 2 hours, cooling to room temperature with the furnace, and taking out a substrate with a multi-element high-activity element coating, wherein the coating contains Fe-Cr, Fe-Al, Cr-Al, and Fe-Cr-Al phases;
[0057] Step 4: immersing the substrate with the multi-element high-activity element coating obtained in step 3 in a 600° C. saturated oxygen concentration liquid lead-bismuth alloy for 100 hours to form a protective Al2O3 oxide layer on the surface of the coating;
[0058] Step 5. Take out the substrate with the multi-element high-activity coating after immersion in step 4, place it in a lead-bismuth alloy cleaning solution prepared by CH3COOH, H2O2 and C2H5OH in a volume ratio of 1:1:1, soak it for 3 hours, then take it out and dry it to obtain a multi-element high-activity coating that forms a self-repairing Al2O3 protective layer.
[0059] Example 6
[0060] This embodiment includes the following steps:
[0061] Step 1: Pre-grind and polish the surface of the ferrite / martensitic steel T91 substrate, then ultrasonically clean and dry it;
[0062] Step 2: bury the ferrite / martensitic steel T91 matrix dried in step 1 in the uniformly mixed Al and Cr powders, and keep a sufficient distance between the matrixes, and then place it in a stainless steel container and seal it; the Al and Cr powders include the following components in mass percentage: Al 17%, Cr 17%, and the balance is Al2O3;
[0063] Step 3, placing the sealed stainless steel container in step 2 in a heating furnace and filling it with high-purity argon, maintaining the pressure at 0.15 MPa, then heating to 900°C at a rate of 10°C / min, keeping the temperature for 2 hours, cooling to room temperature with the furnace, and taking out a substrate with a multi-element high-activity element coating, wherein the coating contains Fe-Cr, Fe-Al, Cr-Al, and Fe-Cr-Al phases;
[0064] Step 4: immersing the substrate with the multi-element high-activity element coating obtained in step 3 in a 500° C. saturated oxygen concentration liquid lead-bismuth alloy for 100 hours to form a protective Al2O3 oxide layer on the surface of the coating;
[0065] Step 5. Take out the substrate with the multi-element high-activity coating after immersion in step 4, place it in a lead-bismuth alloy cleaning solution prepared by CH3COOH, H2O2 and C2H5OH in a volume ratio of 1:1:1, soak it for 3 hours, then take it out and dry it to obtain a multi-element high-activity coating that forms a self-repairing Al2O3 protective layer.
[0066] It has been detected that after the multi-element high-activity element coating forming the self-repairing Al2O3 protective layer in Examples 4 to 6 of the present invention was immersed in a lead-bismuth alloy with saturated oxygen concentration, a large number of Al2O3 diffraction peaks were detected on the surface of the coating, indicating that the coating obtained by the preparation method of the present invention provides a good protective effect on the substrate.
[0067] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a multi-element high-activity coating for forming a self-repairing Al2O3 protective layer in a non-oxygen-controlled lead-bismuth alloy, characterized in that: A FeCrAl coating containing Fe-Cr, Fe-Al, Cr-Al, and Fe-Cr-Al phases is prepared on a substrate containing Fe, and then immersed in a liquid lead-bismuth alloy to form a protective Al2O3 oxide layer on the surface of the coating. The method comprises the following steps: Step 1: Pre-grind and polish the substrate surface, then perform ultrasonic cleaning and drying; Step 2: burying the dried matrix in step 1 into uniformly mixed powders containing Al and Cr, and then placing it in a stainless steel container and sealing it; Step 3, placing the sealed stainless steel container in step 2 in a heating furnace and filling it with protective gas, then heating it to 850°C to 900°C and keeping it for 2h to 3h, cooling it to room temperature with the furnace, and taking it out to obtain a substrate with a multi-element high-activity element coating; Step 4: immersing the substrate with the multi-element high-activity element coating obtained in step 3 in a liquid lead-bismuth alloy at 500° C. to 600° C. for 24 h to 100 h to form a protective Al2O3 oxide layer on the surface of the coating; Step 5: Take out the substrate with the multi-element high-activity coating after soaking in step 4, soak it in a lead-bismuth alloy cleaning solution for 2h to 3h, then take it out and dry it to obtain a multi-element high-activity coating that forms a self-repairing Al2O3 protective layer.
2. The method for preparing a multi-element high-activity coating for forming a self-repairing Al2O3 protective layer in a non-oxygen controlled lead-bismuth alloy according to claim 1, characterized in that: The substrate in step 1 is ferrite / martensitic steel.
3. The method for preparing a multi-element high-activity coating for forming a self-repairing Al2O3 protective layer in a non-oxygen-controlled lead-bismuth alloy according to claim 1, characterized in that: The Al and Cr-containing powder in step 2 includes the following components in mass percentage: Al 15% to 17%, Cr 15% to 17%, and the balance is Al2O3.
4. The method for preparing a multi-element high-activity coating for forming a self-repairing Al2O3 protective layer in a non-oxygen-controlled lead-bismuth alloy according to claim 1, characterized in that: The pressure during the heating and cooling process in step 3 is maintained at 0.15 MPa.
5. The method for preparing a multi-element high-activity coating for forming a self-repairing Al2O3 protective layer in a non-oxygen-controlled lead-bismuth alloy according to claim 1, characterized in that: The protective gas in step 3 is high-purity argon gas with a mass purity higher than 99.99%.
6. The method for preparing a multi-element high-activity coating for forming a self-repairing Al2O3 protective layer in a non-oxygen-controlled lead-bismuth alloy according to claim 1, characterized in that: The heating rate in step 3 is 10°C / min.
7. The method for preparing a multi-element high-activity coating for forming a self-repairing Al2O3 protective layer in a non-oxygen-controlled lead-bismuth alloy according to claim 1, characterized in that: The liquid lead-bismuth alloy in step 4 is saturated with oxygen.
8. The method for preparing a multi-element high-activity coating for forming a self-repairing Al2O3 protective layer in a non-oxygen-controlled lead-bismuth alloy according to claim 1, characterized in that: The lead-bismuth alloy cleaning solution in step 4 is prepared from CH3COOH, H2O2 and C2H5OH in a volume ratio of 1:1:
1.
9. A multi-element high-activity coating for forming a self-repairing Al2O3 protective layer in a non-oxygen-controlled lead-bismuth alloy, characterized in that: The method is prepared by any one of claims 1 to 8.
Citation Information
Patent Citations
Method for improving liquid metal corrosion resistance of martensitic heat-resistant steel
CN104046954A
Preparation method of aluminized coating for improving lead and bismuth corrosion resistance of ferrite-martensite steel
CN113106385A
ODS-FeCrAl protective oxidation film based on high-temperature oxygen saturated liquid lead bismuth corrosion environment and preparation method thereof
CN117385353A